New data on biology of siberian cisco Coregonus sardinella (Coregonidae) from the Anadyr River - Alexander V. Shestakov (Известия ТИНРО)
The data on biology of siberian cisco were collected during its spawning migration in the middle stream of the Anadyr River in September-October of 2010-2011 and during the feeding of mature fish in the Anadyr estuary in June-August of 2011. Besides, the data collected previously in 1987 and 1992 were processed with modern research techniques. The bulk of spawning lake-river cisco is the fish of the age 5+ years with the length 206-218 mm and weight 81-103 g; the feeding cisco in the estuary has mainly the age 4-6+ years, mean length 233.0 ± 4.4 mm and mean weight 119 ± 11 g. Cisco females are larger than males: the maximum size of females is 255 mm with the weight 167 g (age 7+) and the maximum size of males is 249 mm with the weight 160 g (age 7+). Modern age structure of spawning cisco is rejuvenated comparing with that in 1987 and 1992: the maximum age of cisco is now 3 years less, and the average age is 1 year less. The portions of large-sized and medium-sized mature fish became less, too, as well as the average length and weight became 36 mm and 78 g less for females, and 30 mm and 47 g less for males. Recently only 6 age groups of cisco spawn (from 3+ to 8+, mainly 5-6-years) whereas its 8 age groups spawned in the 1980s (from 4+ to 11+, with the modal age 5-8 years). The size decreasing could be partially explained by its higher abundance in recent years and relatively low summer discharge of the Anadyr in 2005-2010. Linear growth of spawning cisco has high rate in the first 5 years, reduces in the 6th year, and decreases abruptly in the 7th year; the growth rate of the lake-river cisco is generally lower than that of the estuarine cisco. Annual linear increments of immature cisco increase significantly in the next year after large runs of chum salmon, but not in a year of large run. The lake-river cisco is an important object of local fishery, with the main fishing grounds at Markovo where it is caught in autumn during its mass spawning migration. Annual landings of cisco are very variable, with significant decreasing in the 2000s. Modern state of the lake-river cisco population is determined mainly by hydrological regime of the river and strength of the chum salmon runs.